A simplified modelling and analysis of six degree of freedom random vibration test. (March 2021) - Zheng, Ronghui; Chen, Huaihai; Angeli, Andrea; Vandepitte, Dirk
Highlights: A simplified mechanical model of a 6-DOF vibration test system is established. Acceleration properties of test article under 6-DOF base vibrations are analysed. Optimal location for control sensors arrangement is discussed. 6-DOF random vibration control method is investigated. Abstract: This paper deals with the modelling and analysis of six degree of freedom random vibration test. It involves an advanced multi-input multi-output random vibration test system where three translational and three rotational motions can be controlled simultaneously. In this work, a mechanical model of the six degree of freedom vibration test system is established such that eight exciters are modelled as spring damper pairs and the shaker table is assumed to be rigid. The acceleration properties of the test article undergoing such six degree of freedom base vibrations are analyzed and the relationships among the absolute acceleration, relative acceleration and base acceleration are derived. In practical applications, typically there is no available angular acceleration sensor for high frequency measurements. Therefore, the three rotational accelerations are obtained from measured translational accelerations of three or more control sensors with a response coordinate transformation matrix. It is shown that the locations of the control points have a significant influence on the response spectral results, which is reflected in the condition number of the output coordinate transformation matrix. The general multi-input multi-output random vibration control method is applied to the 6-DOF random vibration test. A six degree of freedom random vibration test simulation is finally provided.